Using Cover Crops as an Effective Weed Control Method in Southeast Kansas - L. I. Chism; J. A Dille; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2019)
Weed control is important to optimize crop production. This study was conducted to compare the effectiveness of different methods of fall-implemented weed control strategies. These strategies included different cover crop mixes, chemical control, and mechanical control. The cover crop mixes included four different commonly-planted winter cover crops. The chemical control was a fall-applied burndown, and the mechanical control was vertical tillage. We found cover crop mixes that contained cereal rye provided the most weed control, with the chemical control being a close second. Spring oats die during the winter because of the low temperatures. The three cover crop mixes containing spring oats still provided 50% reduction in weed biomass the following spring. However, the fall tillage increased the amount of weed biomass.
Keywords: weed control; cover crops; fall-applied herbicide; vertical tillage